2013
DOI: 10.1001/jamapsychiatry.2013.1388
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Developmental Patterns of Brain Chemistry in Children With Autism Spectrum Disorder

Abstract: IMPORTANCE Autism spectrum disorder (ASD) is a neurodevelopmental disorder with symptoms emerging during early childhood. The pathophysiology underlying the disorder remains incompletely understood. OBJECTIVE To examine cross-sectional and longitudinal patterns of brain chemical concentrations in children with ASD or idiopathic developmental delay (DD) from 3 different age points, beginning early in the clinical course. DESIGN Proton magnetic resonance spectroscopic imaging data were acquired longitudinally fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 56 publications
(73 reference statements)
2
44
0
Order By: Relevance
“…Rojas, 2013); and the cerebellum; striatum and frontal lobe (Hassan et al, 2013). However, other studies have found decreased glutamate/Glx in ASD in regions including the ACC (Bernardi et al, 2011;van Elst, Maier, Fangmeier, & Endres, 2014) the basal ganglia (Horder et al, 2013); frontal and occipital cortex, the cerebellum (Devito et al, 2007) and white matter (Corrigan et al, 2013). Yet other studies have found no significant differences in glutamate / Glx levels between individuals with and without ASD in several different brain regions including parietal lobes (Horder et al, 2013;Page et al, 2006), frontal lobes (Horder et al, 2013) temporal lobes (Devito et al, 2007), and occipital lobes (Robertson, Ratai, & Kanwisher, 2015); the thalamus (Bernardi et al, 2011;Doyle-Thomas et al, 2014;Hardan et al, 2008); hippocampus (Joshi et al, 2012);and cerebellum (van Elst et al, 2014).…”
Section: Glutamate / Glxmentioning
confidence: 98%
“…Rojas, 2013); and the cerebellum; striatum and frontal lobe (Hassan et al, 2013). However, other studies have found decreased glutamate/Glx in ASD in regions including the ACC (Bernardi et al, 2011;van Elst, Maier, Fangmeier, & Endres, 2014) the basal ganglia (Horder et al, 2013); frontal and occipital cortex, the cerebellum (Devito et al, 2007) and white matter (Corrigan et al, 2013). Yet other studies have found no significant differences in glutamate / Glx levels between individuals with and without ASD in several different brain regions including parietal lobes (Horder et al, 2013;Page et al, 2006), frontal lobes (Horder et al, 2013) temporal lobes (Devito et al, 2007), and occipital lobes (Robertson, Ratai, & Kanwisher, 2015); the thalamus (Bernardi et al, 2011;Doyle-Thomas et al, 2014;Hardan et al, 2008); hippocampus (Joshi et al, 2012);and cerebellum (van Elst et al, 2014).…”
Section: Glutamate / Glxmentioning
confidence: 98%
“…48 Following up on children with idiopathic developmental delay, NAA remained reduced at the age of 9 to 10 years. 49 In children with congenital heart disease, NAA increased significantly slower during further development within the third trimester compared with controls. 50 There is further discordance in the literature with regard to autism.…”
Section: Noxa During Pregnancymentioning
confidence: 96%
“…Compared with controls, lower levels of NAA, Cr, and Cho were found. 51,52 In later childhood (at 9-10 years old 49 ) and in adulthood, 53 this was no longer apparent. Other studies found increased values of mI and Cho but no significant differences in NAA compared with controls 54 or even no evidence for brain mitochondrial dysfunction in children with autism 55 ; thus, caution should be exercised in interpreting data concerning agedependent fluctuations in metabolite levels.…”
Section: Noxa During Pregnancymentioning
confidence: 99%
“…Some authors have described reductions of Cr in gray matter, insula, corpus callosum, body of caudate, occipital cortex, and frontal and parietal white matter from subjects of less than 13 years of age (Baruth et al 2013). Another study reported by Corrigan et al (2013) also showed significant Cr decrease in gray as well as in white matter from children with ASDs. Recently, some authors have analyzed the metabolic profile in urine from children with ASDs using two-dimensional nuclear magnetic resonance spectroscopy (2D-NMR) and showed a decreased Cr concentration (Mavel et al 2013).…”
Section: Creatine In Autism Disordersmentioning
confidence: 99%